Partial Purification and Properties of d-Glucosamine 6-Phosphate N-Acetyltransferase from Phaseolus aureus - Vessal, Mahmood (1973)
d-Glucosamine-6-P N-acetyltransferase (EC 2.3.1.4) from mung bean seeds (Phaseolus aureus) was purified 313-fold by protamine sulfate and isoelectric precipitation, ammonium sulfate and acetone fractionation, and CM Sephadex column chromatography. The partially purified enzyme was highly specific for d-glucosamine-6-P. Neither d-glucosamine nor d-galactosamine could replace this substrate. The partially purified enzyme preparation was inhibited up to 50% by 2 × 10(−2)m EDTA, indicating the requirement of a divalent cation. Among divalent metal ions tested, Mg(2+) was required for maximum activity of the enzyme. Mn(2+) and Zn(2+) were inhibitory, while Co(2+) had no effect on the enzyme activity. The pH optimum of the enzyme in sodium acetate and sodium citrate buffers was found to be 5.2. The effect of Mg(2+) on the enzyme in sodium acetate and sodium citrate buffers was particularly noticeable in the range of optimum pH. Km values of 15.1 × 10(−4)m and 7.1 × 10(−4)m were obtained for d-glucosamine-6-P and acetyl CoA, respectively. The enzyme was completely inhibited by 1 × 10(−4)mp-hydroxymercuribenzoate, and this inhibition was partially reversed by l-cysteine; indicating the presence of sulfhydryl groups at or near the active site of the enzyme.